The impact of media theories on the legal regulation of the press: A theoretical study - Sakar Rostam Hussein; Saman Jalal Mawlood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research is an academic effort to present the impact of media theories on the press legal regulation process under the title "The impact of media theories on press legal regulation". It is theoretical research that addresses the procedures of press regulation within the framework of media theories, which are directly influenced by the political system. This research aims to present the forms and procedures of press legal regulation according to media theories, and how each theory has an impact and role in directing and choosing the methods and procedures of legal regulation of the press by authorities and governments according to the differences in the political system followed in the country. The most important conclusions reached by the researcher are that media theories are strongly and directly related to the regulating of the press in societies, and on the other hand, they are directly related to the level of control of the media by desion makers and the state or governments. The characteristics of these theories are reflected in media legislations.